2014
DOI: 10.2147/phmt.s58108
|View full text |Cite
|
Sign up to set email alerts
|

Excessive fasting times: still an underaddressed challenge for African pediatrics and anesthesia?

Abstract: Background: Children are starved before surgery following international preoperative guidelines. Extreme fasting is still reported, but data for Africa are scarce. Starving in hot climates leads to challenges arising from dehydration, hypotension, metabolic disturbances, and complications during induction of anesthesia. The purpose of this study was to evaluate the scope of the problem, identify possible reasons for this, and propose realistic solutions. Methods: We performed eleven prospective audits between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Another study indicated that the mean fasting time for clear liquids is 7.65 times and for solids 2.5 times longer than the preoperative fasting times recommended by ASA [ 18 ]. Children were being starved of water for a mean of 8.5 h, which exceeds the recommendations of all international guidelines [ 19 ]. A study was done by Arun B. on preoperative fasting hours for solids and milk (breast and nonhuman) was between 4 h and 18.75 h (11.25 ± 3.5 h) and clear liquid (water) ranged between 2 h and 18.75 h (9.25 ± 4.25 h) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicated that the mean fasting time for clear liquids is 7.65 times and for solids 2.5 times longer than the preoperative fasting times recommended by ASA [ 18 ]. Children were being starved of water for a mean of 8.5 h, which exceeds the recommendations of all international guidelines [ 19 ]. A study was done by Arun B. on preoperative fasting hours for solids and milk (breast and nonhuman) was between 4 h and 18.75 h (11.25 ± 3.5 h) and clear liquid (water) ranged between 2 h and 18.75 h (9.25 ± 4.25 h) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, in Africa, a caregiver with poor education, who cannot bear the hunger of her child any longer, might feed the child shortly before surgery without informing the Anesthetist [ 19 ]. In our setting most of the caregiver are a child mother or father and they fear that the surgery is difficult unless the child has got eaten as soon as before the procedures.…”
Section: Introductionmentioning
confidence: 99%
“…18 Children were being starved of water for a mean of 8.5 hours, which exceeds the recommendations of all international guidelines. 19 A study was done by Arun B. on preoperative fasting hours for solids and milk (breast and nonhuman) was between 4 h and 18.75 h (11.25 ± 3.5 h) and clear liquid (water) ranged between 2 h and 18.75 h (9.25 ± 4.25 h). 20 Children who had surgery in the morning fasted longer for solids than children who had surgery in the afternoon because of an overnight fast after the evening meal.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Further, in Africa, a caregiver with poor education, who cannot bear the hunger of her child any longer, might feed the child shortly before surgery without informing the Anesthetist. 19 In our setting most of the caregiver are a child mother or father and they fear that the surgery is di cult unless the child has got eaten as soon as before the procedures. Thus, there is now study in our country regarding this topic, the present study aims to assess preoperative fasting adherence to the guidelines and associated factors as a baseline.…”
mentioning
confidence: 99%
“…Pollach et al assessed fasting times at Queen Elizabeth Hospital in Malawi and found that the recommended fasting times were not adhered to and were mostly prolonged [ 7 ]. Dennardt et al, studying the impact of fasting times on glucose, concluded that prolonged fasting times led to metabolic changes including ketoacidosis and low normal blood glucose concentrations in their institution.…”
Section: Introductionmentioning
confidence: 99%